Kegiatan Diskusi pada Pendekatan Saintifik dalam Pembelajaran Sejarah Kelas XI IPS di SMA Negeri 3 Bukittinggi - Mutia Haristi; Zafri Zafri (Jurnal Kronologi, 2020)
This research is motivated because discussion activities have often been carried out on historical subjects, but there are still some discussion steps that are not in accordance with theoretical discussion areas. This study aims to find out more fully the implementation of discussion activities on a scientific approach in learning history both in terms of quantity and quality. This study uses an evaluative method with qualitative research types. The subjects of this study were teachers and students in SMA Negeri 3 Bukittinggi class XI IPS 1, XI IPS2, and XI IPS 3. Data collection in this study by observation and interview. Data processing using interactive analysis techniques. The results of this study stated that the discussion activities in general had been carried out by teachers well, only that there were some things that were not ideal, including:1) the teacher does not always convery the learning objectives. 2) the teacher uses only one type of discussion. 3) no students express their opinions and ideas. This is caused by several faktors, including forgetfulness, time, and less varied learning methods.